Corporate Communication Strategy In Creating The Awareness Of The Covid-19 Through Instagram - Saras Ayunarini; Santi Delliana (Universitas Ahmad Dahlan, 2021)
Following its mission, PT Kereta Commuter Indonesia continues to provide rail transportation services amid the Covid-19 spread in Indonesia. One of the communication strategies implemented by PT. Kereta Commuter Indonesia communicates directly through new media is @commuterline Instagram account using the hashtag #KCILawanCorona to anticipate the spread of the Covid-19. The study aims to determine PT Kereta Commuter Indonesia's communication strategy in preventing the spread of the Covid-19. This study used the descriptive qualitative method. This study will increase awareness based on the Cutlip and Center Theory and help the public anticipate the spread of the Covid-19.Â This research is the communication strategy of PT Kereta Commuter Indonesia includes four steps to solve problems in the Cutlip and Center Theory so that socialization can be accepted and affects commuter line passengers' attitudes. This research includes in-depth interviews, observation, and documentation for data collection. Based on researchers' findings, PT. Kereta Commuter Indonesia implemented a communication strategy in anticipation of the Covid-19 spread. According to the Cutlip and Center Theory written by Broom and Sha (2013), the communication strategy applied is related to the four-step problem-solving process. It has research results, namely to protect internal and external parties of PT. Kereta Commuter Indonesia, provide education, and give appeal to the public, especially commuter line passengers to be more aware, be alert and care to anticipate the spread of the Covid-19.